REAKSI PASAR TERHADAP PENAWARAN SUKUK DAN OBLIGASI DI BURSA EFEK INDONESIA - Fitriani Fitriani (Islamic Economic and Business Journal, 2021)
The aim of this research is to examine the market reaction to the offering of Sukuk and bonds. Testing the market reaction is done by looking at the presence or absence of significant abnormal returns before and after the offer date as well as a comparison of the market reaction to the offering of Sukuk and bonds. This research used the event study method. The population of this study were all publicly traded companies that had been and are still actively listed on the Indonesia Stock Exchange (IDX) for the 2012-2015 period. The sample selection technique used purposive sampling method and obtained as many as 54 issuers offering bonds and 9 Sukuk issuers. Based on the results of statistical testing with a one-sample t-test around the offering date of Sukuk and bonds, it showed that there was an insignificant average abnormal return (AAR). It can be concluded that there was no significant market reaction around the date of offering Sukuk and bonds.